CULTURAL HERITAGE MAINTENANCE: STRATEGIES AND CHALLENGES IN PRESERVING ANCIENT COLLECTIONS AT SINTONG BINGEI LIBRARY, PEMATANG SIANTAR: Pemeliharaan Warisan Budaya : Strategi dan Tantangan dalam Preservasi Koleksi Kuno di Perpustakan Sintong Bingei Pematang Siantar - Hikmah Rosari; Muslih Fathurrahman (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Libraries are important institutions that provide access to various sources of information and knowledge, including books, magazines, journals, newspapers, ancient collections, and digital materials such as e-books, e-journals, and databases. The role of libraries is crucial in meeting the intellectual and educational needs of the community. The main purpose of the library is to provide open access and information services to the community, both for educational, research, and recreational purposes. Over time, libraries have developed into institutions that underlie the development of culture and science, including in maintaining ancient collections. The preservation of ancient collections requires serious attention related to factors of age, materials, environmental conditions, and humidity. This study aims to explore strategies, processes, and obstacles in maintaining ancient collections at the Sintong Bingei Library. Through a qualitative approach with case studies, data were collected through interviews, observations, and document analysis to understand maintenance practices, challenges faced, and recommendations for future policy improvements. The results of the study lead to an understanding of efforts to maintain ancient cultural heritage in the library environment so that it can be seen by future generations and its authenticity is maintained